2019
DOI: 10.1016/j.joca.2018.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of early response genes prevents changes in global joint metabolomic profiles in mouse post-traumatic osteoarthritis

Abstract: Objective: Although joint injury itself damages joint tissues, a substantial amount of secondary damage is mediated by the cellular responses to the injury. Cellular responses include the production and activation of proteases (MMPs, ADAMTSs, Cathepsins), and the production of inflammatory cytokines. The trajectory of cellular responses is driven by the transcriptional activation of early response genes, which requires Cdk9-dependent RNA Polymerase II phosphorylation. Our objective was to determine whether inh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…Metabolomic profiles were also similar between injured and contralateral-to-injured limbs. Our study contributes to a growing body of work that demonstrates that distinct shifts occur in synovial fluid metabolism in the first week post joint injury 25 and are consistent with shifts in whole joint metabolism 44 . Synovial fluid metabolic changes are driven by dysregulation of cartilage and bone metabolism following joint injuries 19 .…”
Section: Discussionsupporting
confidence: 68%
“…Metabolomic profiles were also similar between injured and contralateral-to-injured limbs. Our study contributes to a growing body of work that demonstrates that distinct shifts occur in synovial fluid metabolism in the first week post joint injury 25 and are consistent with shifts in whole joint metabolism 44 . Synovial fluid metabolic changes are driven by dysregulation of cartilage and bone metabolism following joint injuries 19 .…”
Section: Discussionsupporting
confidence: 68%
“…AEA and 2-AG levels were augmented in the synovial fluid of dogs with OA [115]. AEA was also elevated in the joint in a posttraumatic OA mouse model [116]. In contrast to those in healthy volunteers, AEA and 2-AG have been detected in the synovial fluid of OA and RA patients [72].…”
Section: The Role Of Endocannabinoids In Arthritis-associated Pain and Inflammationmentioning
confidence: 97%
“…The authors demonstrated that it was possible to distinguish between ACL surgical samples after 2 weeks and nonsurgical ones, based on their different metabolic signatures [3]. In another study, June et al induced noninvasive ACL injury in mice by applying a mechanical load to their ankles and investigated the resultant metabolic alterations in microdissected joint tissues following ACL injury by HPLC-MS. Their results showed that the ACL injury caused a broad range of metabolic changes, including the upregulation of retinoid metabolism, phospholipid biosynthesis, hydroxyproline degradation, and anandamide metabolism [19]. Similar metabolomics studies have also been performed on the synovial fluid samples obtained from patients with osteoarthritis or rheumatoid arthritis [20, 21].…”
Section: Discussionmentioning
confidence: 99%